Pemberdayaan UMKM melalui pelatihan pemasaran dan standarisasi produk halal di Desa Sidang Muara Jaya - Kurniati, Erlin; Fajria, Amelia; Cahyadi, Dwi; Irfansyah, Muhammad Nur; AS, Obi Permana; Latifah, Latifah; Mazida, Farah Revi; Ananda, Pinka Ollyvia; Azzahra, Intan (Nur Science Institute, 2024)
The main issue in Sidang Muara Jaya Village, Rawa Jitu Utara District, is the low absorption of products from Micro, Small, and Medium Enterprises (MSMEs). By understanding the challenges faced, it is hoped that MSME actors can devise more effective strategies to enhance the appeal and visibility of Kerupuk Komplang products while encouraging the community to appreciate and purchase local products. This community service initiative was implemented through socialization, mentoring, and creating halal logos and a brand unique to Sidang Muara Jaya Village. The outcomes of this initiative successfully improved the knowledge and skills of MSME actors in the community. The insights gained regarding the importance of absorbing local products can help stimulate the economy of Sidang Muara Jaya Village. However, the initiative also identified several issues, including inadequate transportation and distribution facilities, a lack of product innovation, ineffective marketing strategies, insufficient training and skills, and competition from imported products.